Cisplatina induz um padrão de toxicidade hepatorrenal diferente em ratos neonatos e adultos - Fulco, Bruna da Cruz Weber (2018)
Cisplatin is a widely used chemotherapeutic to treat several types of tumors on both adult and pediatric subjects. Although cisplatin is widely used, its use is associated with serious toxic effects, including nephrotoxicity and hepatotoxicity. Thus, the present study investigated the effects caused by cisplatin acute administration on newborn Wistar rats and the differences in the drug toxicity compared to adult rats. The study was carried out using male and female Wistar rats 10 and 60 day-old (CEUA nº 2699300315). Rats received cisplatin at doses of 5 and 10 mg/kg, by the intraperitoneal (ip.) route, whereas the control group received saline (0.9%, ip.). After 24 h of cisplatin/saline administration, the animals were killed and samples of blood, liver, and kidneys were collected for ex vivo analyses. Markers of renal (urea) and hepatic damage (alanine aminotransferase and aspartate aminotransferase activities) were determined in the serum samples. Parameters of oxidative stress (levels of reactive oxygen species, lipid peroxidation, carbonyl protein, non-protein thiols (NPSH)); activities of antioxidant enzymes (superoxide dismutase, catalase (CAT), glutathione peroxidase, glutathione- S-transferase and glutathione reductase) and activities of sulfhydryl enzymes (δ-aminolevulinate dehydratase (δ-ALA-D) and Na +, K + - ATPase) were determined in samples of liver and kidney of rats. The levels of proteins related to oxidative stress and apoptosis were also determined in samples of liver and kidney of rats at both ages. The cisplatin acute administration caused hepatorenal toxicity in both neonatal and adult rats. However, the pattern and the severity of the damages were different among the ages and tissues. Newborn rats presented greater oxidative metabolic damage when compared to adult rats, characterized by an increase in reactive species and carbonyl protein levels, lower NPSH content, and greater inhibition of δ-ALA-D and CAT activities. In addition, a faster molecular response was found in the protein levels involved with apoptosis and response to oxidative stress. In conclusion, the data from this study show that the pattern of cisplatin toxic effects was different among the ages and tissues of rats. The present study also revealed that newborn rats are more sensitive to treatment with cisplatin for at least the first 24 h and further showed that liver damage, at least in the beginning, was greater than renal damage in adult rats. Thus, the present study demonstrated that there are differences in the body response to acute exposure of cisplatin among adult and newborn rats, reinforcing the need for further studies on children response to chemotherapy and possible effective strategies to minimize the damage caused by cisplatin.